2010
DOI: 10.1186/1471-2148-10-94
|View full text |Cite
|
Sign up to set email alerts
|

The Trichoderma harzianum demon: complex speciation history resulting in coexistence of hypothetical biological species, recent agamospecies and numerous relict lineages

Abstract: BackgroundThe mitosporic fungus Trichoderma harzianum (Hypocrea, Ascomycota, Hypocreales, Hypocreaceae) is an ubiquitous species in the environment with some strains commercially exploited for the biological control of plant pathogenic fungi. Although T. harzianum is asexual (or anamorphic), its sexual stage (or teleomorph) has been described as Hypocrea lixii. Since recombination would be an important issue for the efficacy of an agent of the biological control in the field, we investigated the phylogenetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 53 publications
(63 reference statements)
4
100
0
2
Order By: Relevance
“…The next majority of strains (18) were identified as members of the Harzianum-Catoptron Clade [37]. The phylogenetic analysis of tef1 locus revealed that seven strains formed a separated clade inside of -T. harzianum species complex‖ (H. ‗pseudoharzianum' sensu Druzhinina et al [36]), possessing a unique tef1 allele ( Figure 1B), that was not detected in rhizosphere of C. arabica [19].…”
Section: Diversity Of Endophytic Trichodermamentioning
confidence: 99%
“…The next majority of strains (18) were identified as members of the Harzianum-Catoptron Clade [37]. The phylogenetic analysis of tef1 locus revealed that seven strains formed a separated clade inside of -T. harzianum species complex‖ (H. ‗pseudoharzianum' sensu Druzhinina et al [36]), possessing a unique tef1 allele ( Figure 1B), that was not detected in rhizosphere of C. arabica [19].…”
Section: Diversity Of Endophytic Trichodermamentioning
confidence: 99%
“…Trichoderma harzianum T S1 belongs to the deuteromycetes Amon, Trichosporon Gang, Trichosporon mesh, sticky spore fungi (Druzhinina et al, 2010) and is widely used as a seed treatment to control disease, promote growth, and increase plant yield (Mastouri et al, 2010;Druzhinina et al, 2010). This fungus releases cell wall-degrading enzymes, which combat plant pathogens through a variety of mechanisms (Ghisalbert and Sivasithamparam, 1991;Monte, 2001;Monteiro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Following the classification of Druzhinina et al (2010), we observed some ITS sequence variation among the isolates clustering with T. harzianum. The formation of subgroups within T. harzianum is recognized, since it is regarded as a species complex (Kullnig et al 2000).…”
Section: Was T Viridementioning
confidence: 94%
“…With the development of molecular phylogeny, the genus Trichoderma has been grouped into taxonomic sections (Bissett 1984); based on phylogenetic clades (Druzhinina et al 2010). As an extension of this work, Druzhinina and colleagues (2005) developed a DNA barcode for molecular identification of Trichoderma species, called TrichOKEY.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation